Individual risk tolerance and herding behaviors in financial forecasts. (16th July 2019) - Christoffersen, Jeppe; Stæhr, Simone
Abstract: Financial analysts tend to demonstrate herding behavior, which sometimes compromises accuracy. A number of explanations spanning rational economic logic, cognitive biases, and social forces have been suggested. Relying on an experimental setting where participants forecast future earnings from a rich information set, we posit and obtain support for individual risk tolerance (or lack thereof) as an explanatory variable for herding behaviors. Specifically, less risk‐tolerant individuals forecast with less boldness and instead issue forecasts in agreement with the consensus forecast. The results are argued to be at least partially a product of cognitive biases and an intuitive reaction to uncertainty.